Myoplastics in amputations and reamputations of the shin - Shevchuk, Victor; Bezsmertniy, Yuriy; Kirichenko, Vasyl’ (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
On the basis of observation of 186 patients, the prevalence and character of pathology of the shin stump after traditional plasty methods were studied. The devised methods of myoplasty on the basis of fixation of muscles to bone stumps are directed to decrease negative amputation manifestations: muscular retraction with ledged bone stumps, excessive mobility of the fibula and its valgus deviation, contouring of the tibial crest, fixation of muscles to the scar. The suggested techniques of myoplasty improve firmness, support, endurance and functionality of amputation stumps, formed on the shin level.